Principio de igualdad y no discriminación en la categorización de los regímenes rimpe y general - Ruiz Mendoza, Jefferson Antonio (2025)
In 2021, the tax regime called the Simplified Regime for Entrepreneurs and Popular Businesses (RIMPE) was created to simplify the way in which both Value Added Tax and Income Tax are declared and paid. This new regime aims to categorize taxpayers differently by establishing specific criteria for inclusion or exclusion. Since in inception in 2021, the RIMPE regime has undergone several reforms for various reasons. Given that taxation is a matter affecting Ecuador’s economy-funding public services and infrastructure-this scientific article employs a mixed qualitativequantitative approach. This methodology allows for an analysis of the socio-legal effects, the responsibilities of the state, the advantages and disadvantages of applying the Internal Tax Regime Law, as well as a documentary analysis of Ecuadorian legal frameworks and bibliographic sources related to both the RIMPE and General Regimes. As a result, it was determined that the Internal Revenue Service (SRI) is not applying the law in a strictly literal manner but rather interpreting it at its own discretion. Consequently, the core issue arises from the issuance of administrative acts that violate the constitutional principle of equality and nondiscrimination, as they unjustifiably discriminate against a specific group of taxpayers (those who previously held a taxpayer identification number-RUC) without a clear legal basis.